2014
DOI: 10.1016/j.physd.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure of Sinai–Ruelle–Bowen measures

Abstract: Sinai-Ruelle-Bowen measures are the only physically observable invariant measures for billiard dynamical systems under small perturbations. These measures are singular, but as it was noted in [1], marginal distributions of spatial and angular coordinates are absolutely continuous. We generalize these facts and provide full mathematical proofs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…We note that the stronger linear response property can be established in certain situations [16], but that linear response is not required for the purposes of this paper.…”
Section: Nonuniformly Hyperbolic Fast Dynamicsmentioning
confidence: 99%
“…We note that the stronger linear response property can be established in certain situations [16], but that linear response is not required for the purposes of this paper.…”
Section: Nonuniformly Hyperbolic Fast Dynamicsmentioning
confidence: 99%
“…There is no need to introduce the homogeneous strips if lim x→0 + T (x) < ∞. In the case when lim x→0 + T (x) = ∞, the function f (x, y) defined in (16) vanishes at x = 0. If Condition (h2) also holds, we choose a constant b > 0 such that…”
Section: Verification Of Assumptions (H1) -(H4)mentioning
confidence: 99%
“…Recall that S 1 consists of vertical singularity lines and ∂Q, and thus d(x, S 1 ) min{x, y, 1 − y} for x = (x, y) with x ∈ I 00 . By the definition of f (x) in (16), we obtain that f (x) = f (x) = 1…”
Section: Verification Of Assumptions (H1) -(H4)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Green-Kubo type formula was proved, and it was shown that the current generated by the forced flow is closely related to the strength of the force. Very recently, Chernov and Korepanov investigated in [CK13] the linear response for Sinai billiards under external forces (without twisting). In this paper, we consider the dynamics of the Sinai billiard on the table Q, but subject to more general forces P = (F, G) both during flight and at collisions.…”
Section: Introductionmentioning
confidence: 99%